Peran Sistem Informasi Pada Prosedur Administrasi Keuangan Perbankan Di Kota Pematangsiantar - Beatrice Nathania; Eka Pratiwi Septania Parapat; Debora Silvia Hutagalung (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2021)
Information system based on technology is one of the efforts made by the management to improve company performance. The purpose of this research is to see the role of information systems in the implementation of banking activities. Data collection methods used are interviews and observation. The collected data will be tested for the validity and validity of the data first. The analytical technique used is a qualitative analysis technique in which the researcher acts as an analytical tool. In this case the researcher collects as much data as possible found in the field and then analyzes the data. From the results of the analysis, it is concluded that banking companies that have adopted technology in their operational activities will have a positive impact, namely increasing company performance. The company's performance can be seen from the increase in profits, increase in customers, as well as increased public confidence in the banking product.